Lithium hydride as an efficient reagent for the preparation of 1,2-anhydro inositols: does the reaction proceed through 'axial rich' conformation? - Sarkar, Nitai; Sardessai, Richa S.; Shashidhar, Mysore S.; Tamboli, Majid I.; Gonnade, Rajesh G. (Carbohydrate Research, 2018)
scyllo-Inositol derived 1,2-trans-diequatorial halohydrins can be efficiently converted to the corresponding epoxides in the presence of lithium hydride. The structure of one of the epoxides was determined by single crystal X-ray diffraction analysis. This provides a potential route for the preparation of ring modified inositol derivatives. DFT calculations suggest that this epoxide formation could be proceeding through the intermediacy of the cyclohexane ring-inverted axial-rich conformer (1,2-trans-diaxial halohydrin). This is supported by the results of DFT calculations on the formation of inositol orthoformate, where the product is locked in the axial-rich conformation, while the starting inositol has the equatorial-rich conformation.